The Role of Pedometer Based Walking Exercise To Quadriceps Muscle, Quality of Life, Benefit, and Cost in Stable COPD Patient - Jatu Aviani; Suradi Suradi; Ana Rima (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Quadriceps muscle dysfunction in chronic obstructive pulmonary disease (COPD) is caused by systemic or local inflammation, hypoxia, hypercapnia, corticosteroid use, nutritional depletion, anabolic/catabolic hormone imbalances, oxidative stress, genetic susceptibility, and decreased daily activity. Decreased quadriceps muscle strength reduces exercise capacity, physical activity, increases shortness of breath, and decreases quality of life. Exercise trainng of walking increases the quadriceps muscle strength and overcomes deconditioning. The purpose of this study was to analyze effect of pedometer-based exercise on quadriceps muscle strength, quality of life, benefits, and cost on patients with stable COPD. Methods: A clinical study with quasi-experimental pre-post test control group design using consecutive sampling was performed in patients with stable COPD at Dr. Moewardi Hospital from September to November 2018. Subjects were divided into intervention group which were given pedometer based walking exercise for six weeks and control group with standard rehabilitation. Quadriceps muscle strength, SGRQ score, LCADL score, and cost effectiveness were measured before and after exercise. Results: Twenty-seven of stable COPD patients were included in this study. The intervention groups showed increased quadriceps muscle strength (2,58+0,49), decreased SGRQ scores (23,39+6,60), decreased LCDAL scores (-5,69+2,18), and cost effectiveness compared to control group (P